2016
DOI: 10.1016/j.btre.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of arsenic-resistant bacteria and possible application in bioremediation

Abstract: HighlightsIsolation of two rod-shaped Gram-positive bacteria.Isolates tolerate up to 4500 ppm and 550 ppm concentration of arsenate and arsenite.Bacteria mediated arsenic bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(81 citation statements)
references
References 33 publications
4
71
0
6
Order By: Relevance
“…This molecular technique has been extensively used for bacterial phylogeny, thereby leading to the establishment of large public-domain databases and its vast exploitation in the identification of bacteria (Khusro and Aarti 2015). The identification of bacterium using 16S rRNA sequencing in the present investigation is consistent with other related current reports (Dash et al 2015;Dey et al 2016). …”
Section: Discussionsupporting
confidence: 89%
“…This molecular technique has been extensively used for bacterial phylogeny, thereby leading to the establishment of large public-domain databases and its vast exploitation in the identification of bacteria (Khusro and Aarti 2015). The identification of bacterium using 16S rRNA sequencing in the present investigation is consistent with other related current reports (Dash et al 2015;Dey et al 2016). …”
Section: Discussionsupporting
confidence: 89%
“…Тому вивчення біогенезу H 2 S бактеріями важливе для розроблення ефективних і рентабельних біологічних способів регулювання рівня сполук сульфуру та металів у забруднених середовищах. Відбирання виділених із техногенно змінених екотопів, адаптованих до несприятливих умов штамів мікроорганізмів,особливо актуальне завдання для створення нових способів очищення довкілля (Wang et al, 2008;Zhuang et al, 2012;Iwahori et al, 2014;Limcharoensuk et al, 2015;Mustapha & Halimoon, 2015;Rabus et al, 2015;Si et al, 2015;Dey et al, 2016;Kiran et al, 2017). Мета статтівивчити вплив солей плюмбуму, купруму (ІІ), феруму (ІІ) та мангану (ІІ) на утворення гідроген сульфіду сульфат-і сірковідновними бактеріями, виділеними з води озера Яворівське, оцінити ефективність їх використання для очищення середовищ, збагачених органічними сполуками, від гідроген сульфіду та важких металів.…”
Section: вступunclassified
“…Ефективність мікробіологічного осадження іонів металів у вигляді МеS гідроген сульфідом, утвореним клітинами сульфат-і сірковідновних бактерій, залежить від концентрації гідроген сульфіду, який вони утворюють у процесі дисиміляційної сульфат-або сіркоредукції (Wang et al, 2008;Richter et al, 2012;Gudz et al, 2011;Moroz, 2013;Kuznetsov et al, 2015;Kiran et al, 2017). З іншого боку, інтенсивність анаеробного дихання мікроорганізмів у забруднених екотопах визначається рівнем їх адаптації до несприятливих умов довкілля (Zhuang et al, 2012;Iwahori et al, 2014;Viti et al, 2014;Limcharoensuk et al, 2015;Mustapha & Halimoon, 2015;Rabus et al, 2015;Si et al, 2015;Dey et al, 2016;Kiran et al, 2017). Штами сульфатвідновних бактерій Desulfovibrio desulfuricans ІМВ K-6, Desulfovibrio sp.…”
Section: обговоренняunclassified
“…It has been reported that, arsenite and arsenate forms are poisonous to environment as well as human health (Dey et al 2016). The activity that leads to As pollution are mining, smelting, ore processing, and utilization of arsenic-based pesticides or herbicides, and arsenic contaminated water when irrigated posed heavy contamination of soil, especially in cultivated land ecosystem (Shagol et al 2014).…”
Section: Introductionmentioning
confidence: 99%